1/10+1/11+1/12+...+1/99+1/100
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1+(-2)+3+(-4)+5+(-6)+7+(-8)+9+(-10)+11+(-12)
=(1+3+5+7+9+11)+[(-2)+(-4)+(-6)+(-8)+(-10)+(-12)]
= 36+-42
=-6
(-1)+2+(-3)+4+(-5)+6+(-7)+8+(-9)+10+(-11)+12
=[(-1)+(-3)+(-5)+(-7)+(-9)+(-11)]+(2+4+6+8+10+12)
=(-36)+42
=6
\(S=\frac{1}{10.11}+\frac{1}{11.12}+...+\frac{1}{99.100}\)
\(\Rightarrow S=\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+...+\frac{1}{99}-\frac{1}{100}\)
\(\Rightarrow S=\frac{1}{10}-\frac{1}{100}\)
\(\Rightarrow S=\frac{99}{100}\)
\(S=\frac{1}{10.11}+\frac{1}{11.12}+....+\frac{1}{99.100}\)
\(=\frac{11-10}{10.11}+\frac{12-11}{11.12}+...+\frac{100-99}{99.100}\)
\(=\frac{11}{10.11}-\frac{10}{10.11}+\frac{12}{11.12}-\frac{11}{11.12}+....+\frac{100}{99.100}-\frac{99}{99.100}\)
\(=\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+....+\frac{1}{99}-\frac{1}{100}\)
\(=\frac{1}{10}-\frac{1}{100}=\frac{9}{100}\)
\(C=-\dfrac{9}{10}\left(-\dfrac{10}{11}\right)\left(-\dfrac{11}{12}\right)...\left(-\dfrac{98}{99}\right)\left(-\dfrac{99}{100}\right)\)
Ta thấy C có \(\left(100-10\right):2+1=46\) thừa số nên số dấu âm là chẵn
Vậy \(C=\dfrac{9}{10}\cdot\dfrac{10}{11}\cdot\dfrac{11}{12}\cdot...\cdot\dfrac{99}{100}=\dfrac{9}{100}\)
\(A > \frac{1}{10} + (\frac{1}{100}+...+ \frac{1}{100}) \)
\(= \frac{1}{10} + \frac{99}{100} = \frac{109}{100} > 1\)
\(=> A > 1\)
1/
\(10A=\frac{10^{12}-10}{10^{12}-1}=1-\frac{9}{10^{12}-1}<1\)
\(10B=\frac{10^{11}+10}{10^{11}+1}=1+\frac{9}{10^{11}+1}>1\)
$\Rightarrow 10A< 1< 10B$
$\Rightarrow A< B$
2/
\(C=\frac{10^{99}+5}{10^{99}-8}=1+\frac{13}{10^{99}-8}\)
\(D=\frac{10^{100}+6}{10^{100}-4}=1+\frac{10}{10^{100}-4}\)
So sánh \(\frac{13}{10^{99}-8}=\frac{130}{10^{100}-80}> \frac{130}{10^{100}-4}> \frac{10}{100^{100}-4}\)
$\Rightarrow 1+\frac{13}{10^{99}-8}> 1+\frac{10}{100^{10}-4}$
$\Rightarrow C> D$